Character Education Values in Pupuh Pucung from Ki Hadjar Dewantara’s Educational Perspective - Wilky Leonady; Uus Karwati; Reni Haerani (OSTINATO: Journal of Music Study and Research, 2025)
This study examines Pupuh Pucung as a culturally grounded medium for character education by analyzing its moral values through the educational philosophy of Ki Hadjar Dewantara. Using a qualitative descriptive approach with content analysis, this study analyzes selected Pupuh Pucung texts to identify character values and interpret their alignment with the principles of Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani. The results show that Pupuh Pucung contains core character values, including perseverance, discipline, responsibility, self-reflection, togetherness, and social awareness, which are conveyed through simple, rhythmic, and easily memorized poetic structures. These values function not merely as moral advice but as experiential narratives that encourage internalization through reflection and social context. The analysis further reveals that Pupuh Pucung operationalizes Ki Hadjar Dewantara’s educational principles by presenting moral exemplars, fostering collective learning motivation, and encouraging learners’ autonomy. This study concludes that Pupuh Pucung is not only a traditional literary form but also a pedagogical text with strong relevance for character education based on local wisdom. The findings imply that integrating Pupuh Pucung into educational practices can strengthen moral awareness, cultural identity, and holistic character development in both formal and nonformal learning contexts. Future research is recommended to explore the empirical implementation of Pupuh Pucung–based learning models and their impact on students character development.